Development of hierarchical ranking strategy for the asphalt skeleton in semi-flexible pavement - Saboo N.; Ranjeesh R.; Gupta A.; Suresh M. (My University, 2025)
This study evaluates the suitability of seven different asphalt mixes, prepared at a wide range of binder content (2–5%), to be used for semi-flexible pavement. A hierarchical list of tests, including draindown, air void content, voids in coarse aggregate (VCA) ratio, permeability and Cantabro loss have been selected for accepting/rejecting the mixes based on limiting values assigned to each test parameter. Indirect tensile strength (ITS) test is finally used as a fatigue performance criteria to evaluate the relative performance of the mix. This study also proposes a simple methodology of ranking the mixes based on the priority given to the ‘type’ of test. The proposed method tends to eliminate the constraint imposed by the limiting criteria under each test. The hierarchical method of eliminating/selecting mixes was found to be appropriate for arriving at the mixes with most desirable properties as a surface layer in semi-flexible pavement. Eight mixes including M-1 (BSI): 3.5%, M-1: 4%, M-2 (Boundy): 3.5%, M-3 (Densiphalt 8): 4%, M-3: 4.5%, M-4 (Densiphalt 12): 4%, M-4: 4.5% and M-5 (Setyawan): 4% were found to satisfy all the limiting criteria imposed on various test parameters. It was shown, using a suitable example of six different cases, that the final rank based on the proposed methodology is a function of the priority given to the type of test by the designer. Out of the eight mixes, meeting all the desirable properties, M-4: 4%, M-1: 4% and M-4: 4.5% were ranked highest and are recommended to be used for semi-flexible pavement. © 2018 Elsevier Ltd